Les facteurs non hémodynamiques de variation de la pression artérielle chez d’anciens sportifs demeurés actifs - LAWANI, MOHAMED MANSOUROU (My University, 2007)
Objectives. – The aims of this cross-sectional study were: 1) To determinate the parameters that discriminate subjects with high blood pressure from those with a low one, in a sample of former sports men still active; 2) To identify the non hemodynamic determinants of the blood pressure in the same sample. Methods. – Tree adiposity indexes, the indirect V_ O2max, the total plasma cholesterol, the resting heart rate, the blood pressure, the neck circumference were measured in 129 elderly sports men of 40 years and over. The history of physical activity and cardiovascular disease were also investigated. Results. – The half of the sample was at a hypertensive risk. The means of the body mass index, the sum of the skinhold thickness, the resting heart rate, the total plasma cholesterol, the diastolic blood pressure and the pulsed pressure were higher (P < 0.05) in the subjects with high blood pressure. After adjusting for age, the body mass index and the resting heart rate explain together, respectively 11% (P = 0.006) and 18% (P = 0.005) of the variations in the systolic and the diastolic blood pressure.Conclusion. – In the studied group, the overweight, a high resting heart rate, and the hypercholesterolemia were associated with the hypertensive risk. To improve their blood pressure profile, these active former sports men must use continuous and moderate exercises, lasting more than the former ones.
Keywords: Sport; Pression artérielle; Facteur de risque; Désentraînement